Is there a role for stool metabolomics in cystic fibrosis?. Issue 8 (August 2016) - Kaakoush, Nadeem O; Pickford, Russell; Jaffe, Adam; Ooi, Chee Y
Abstract: A number of studies utilizing metabolomics have focused on the pathophysiology of cystic fibrosis (CF) lung disease. Here, we performed fecal metabolomics on pancreatic insufficient (PI) and sufficient (PS) children with CF and compared them with healthy controls (HC). Fecal metabolomics can differentiate between PS‐CF and PI‐CF. We identified a potential biomarker of disease severity or cystic fibrosis transmembrane conductance regulator function ( m/z, 463.247; retention time, 0.570717 min) that discriminates between HC versus PS‐CF versus PI‐CF. We also identified lipoyl‐GMP as a potential novel inflammatory biomarker, and elevation in fecal glycerol 1, 2‐didodecanoate 3‐tetradecanoate may provide clues to the pathogenesis of intestinal inflammation. For the first time, we demonstrate the potential applications of fecal metabolomics in CF.